Future living arrangements of Singaporeans with age-related dementia - Thompson, James P. (2014)
Background: With rapid aging, Singapore faces an increasing proportion of the population with age-related dementia. We used system dynamics methodology to estimate the number and proportion of people with mild, moderate, and severe dementia in future years and to examine the impact of changing family composition on their likely living arrangements. Methods: A system dynamics model was constructed to estimate resident population, drawing birth and mortality rates from census data. We simulate future mild, moderate, and severe dementia prevalence matched with estimates of total dementia prevalence for the Asian region that includes Singapore. Then, integrating a submodel in which family size trends were projected based on fertility rates with tendencies for dependent elderly adults with dementia to live with family members, we estimate likely living arrangements of the future population of individuals with dementia. Results: Though lower than other previous estimates, our simulation results indicate an increase in the number and proportion of people in Singapore with severe dementia. This and the concurrent decrease in family size point to an increasing number of individuals with dementia unlikely to live at home. Conclusions: The momenta of demographic and illness trends portend a higher number of individuals with dementia less likely to be cared for at home by family members. Traditions of care for frail elderly found in the diverse cultures of Singapore will be increasingly difficult to sustain, and care options that accommodate these demographic shifts are urgently needed.